Longevity of Cleruchoides noackae (Hymenoptera: Mymaridae), an Egg Parasitoid of Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae), with Various Honey Concentrations and at Several Temperatures - Souza, Amanda Rodrigues De [UNESP]; Candelaria, Murici Carlos [UNESP]; Barbosa, Leonardo Rodrigues; Wilcken, Carlos Frederico [UNESP]; Campos, Juliana M.; Serrão, José Eduardo; Zanuncio, José Cola (De Gruyter, 2016)
Thaumastocoris peregrinus Carpintero and Dellapé (Hemiptera: Thaumastocoridae), damages eucalyptus plants by sucking their sap. This pest can be controlled by releases of the egg parasitoid Cleruchoides noackae Lin and Huber (Hymenoptera: Mymaridae). Increasing the survival of this parasitoid is critically important for its mass rearing in order to release large numbers in integrated programs to manage T. peregrinus. The aim of this study was to evaluate the longevity of C. noackae adults fed various honey concentrations at 6 constant temperatures. The longevity of C. noackae was studied by keeping adults in a 1st experiment with 100, 50, or 10% honey solution, with distilled water, or without water and food in climate-controlled chambers at 25 ± 2 °C, 70 ± 10% RH, and a 12:12 h L:D photoperiod and-in a 2nd experiment-with 100% honey at constant temperatures of 15, 18, 21, 25, 28, or 31 °C in a climatic chamber at 70 ± 10% RH and a 12:12 h L:D photoperiod. Each adult parasitoid was held individually in a glass tube capped with plastic wrap under the conditions described, and the survival of adults was recorded daily. The longevity of C. noackae varied with food and temperature such that longevity was enhanced by all honey concentrations and temperatures of 25 °C and below. When fed honey, this parasitoid lived 2 to 3 fold longer when kept at 15, 18, 21, and 25 °C than at 28 and 31 °C. Thus, the parasitoid C. noackae should be mass reared with honey at temperatures from 15 to 25 °C for subsequent distribution of parasitoid adults in eucalyptus plantations for suppressing T. peregrinus. .
Keywords: Biological control; Eucalyptus; Laboratory rearing